Increased lean body mass as an early indicator of olanzapine-induced weight gain in healthy men. (January 2015) - Daurignac, Elsa; Leonard, Kenneth E.; Dubovsky, Steven L.
Abstract : One of the primary limitations of many psychiatric medications is weight gain, the mechanism of which remains to be fully elucidated. We conducted a 2-week double-blind placebo-controlled study on weight gain with olanzapine, which is frequently but unpredictably associated with this side effect, to address the possible mechanisms of weight gain independent of changes in the psychiatric condition for which it is prescribed. Healthy male volunteers were randomly assigned to olanzapine (5 mg/day for 7 days, then 10 mg/day for 7 days) or a matching placebo. Of the 24 participants, 19 completed the study (olanzapine, n =13; placebo, n =6). Body weight, glucose, triglyceride, total cholesterol, lipid, leptin, insulin, and aldosterone levels, resting metabolic rate, body composition, physical activity, and 24-h dietary intake were assessed. A significant increase in weight as well as triglyceride, insulin, and leptin levels were found in the olanzapine group as a whole. In participants receiving olanzapine who actually gained weight ( n =8), lean but not fat mass increased, as did insulin, fasting glucose, total cholesterol, low-density lipoprotein, and non-high-density lipoprotein levels, whereas aldosterone levels decreased. There were no significant metabolic or endocrine changes in participants receiving placebo or in those receiving olanzapine who did not gain weight. Early metabolic changes appear to be independent of accumulation of fat.